Paper containing aramid pulp suitable for electrochemical cells and electrochemical cells made therefrom

By using a high content of flax fiber pulp and a low content of PVP surface coating in the electrochemical cell separator paper, the problem of poor performance of electrochemical cell separator paper in the prior art at high temperatures is solved, and the high tension resistance and flame protection performance are improved.

JP7656026B2Active Publication Date: 2025-04-02DUPONT SAFETY & CONSTRUCTION INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023507523
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-04
Filing Date
2020-09-22
Publication Date
2025-04-02
Estimated Expiration
2040-09-22

AI Technical Summary

Technical Problem

The prior art is difficult to provide electrochemical cell separators suitable for high temperature operation, as well as materials with high tension and flame protection.

Method used

90-99% flax fiber slurry is used. The flax fiber slurry contains 10-2000 nanometer flax polyester fiber bundles with a length of 0.2-3 mm and a characteristic surface area of ​​3-40 square meters/g. 1-10% polyvinylpyrrolidone (PVP) is added as the surface coating to the flax fiber slurry, and the coating does not bind to the fiber chemically or electrostatically.

Benefits of technology

The high temperature stability of electrochemical cell separator paper is achieved, the tension resistance and flame protection performance of the paper are improved, making it suitable for the separation of electrochemical cells and heat insulation and protection in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656026000004
    Figure 0007656026000004
  • Figure 0007656026000005
    Figure 0007656026000005
  • Figure 0007656026000006
    Figure 0007656026000006
Patent Text Reader

Abstract

A paper suitable for use as a separator or a thermal insulator or fire retardant for use in or with an electrochemical cell, and an electrochemical cell containing the paper, wherein the paper has 90 to 99 weight percent aramid fiber pulp containing aramid polymer fibrils and 1 to 10 weight percent polyvinylpyrrolidone present as a coating on the surface of the fibers, and the paper has a thickness of 10 to 40 micrometers and a tensile strength of at least 15 megapascals.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Priority Data This application is a continuation-in-part of U.S. patent application Ser. No. 16 / 166,296, filed Oct. 22, 2018, and claims priority to U.S. Provisional Patent Application Ser. No. 62 / 580,009, filed Nov. 1, 2017.

[0002] The present invention relates to a base paper comprising aramid pulp and polyvinylpyrrolidone, which when coated with a resin is useful as a friction material. In some other embodiments, the paper itself, the base paper, is suitable for use as an electrolyte separator in an electrochemical cell or as a thermal or flame retardant. [Background technology]

[0003] U.S. Patent No. 5,532,059 to Lee discloses a fiber pulp of a combination of poly(p-phenylene terephthalamide) and poly(vinylpyrrolidone) along with a method for making the same. The method requires that the poly(p-phenylene terephthalamide) polymerization reaction be carried out in the presence of poly(vinylpyrrolidone), and the product is an improved pulp with increased fibrils and an absence of fiber patterns.

[0004] U.S. Pat. No. 3,036,950 to Martin describes a method for depositing a water-dispersible resin onto beaten cellulose pulp fibers, which comprises first dispersing polyvinylpyrrolidone in an aqueous slurry of the fibers and then dispersing the resin in the slurry, where polyvinylpyrrolidone is added in an amount of at least about 0.05% by weight based on the dry weight of the pulp fibers.

[0005] Ramachandran, U.S. Pat. No. 6,139,688, teaches coated aramid fibers, the coating being a small amount of chitosan, the coated fibers being useful in the manufacture of improved friction papers.

[0006] There is a continuing need to provide papers for friction applications as well as papers suitable for use in or with electrochemical cells; i.e., papers suitable as separators in electrochemical cells that can operate at very high temperatures (commonly known as battery separators); or papers that can be used as insulation or flame barriers in or around electrochemical cells or electrochemical modules that contain multiple electrochemical cells, where the tensile strength of the paper can be increased. Summary of the Invention [Means for solving the problem]

[0007] The present invention provides a paper suitable for use as a separator or insulator in an electrochemical cell, comprising: a) 90 to 99 weight percent aramid fiber pulp, based on the total weight of the paper, the aramid fiber pulp comprising aramid polymer fibrils, the aramid polymer fibrils having i) a diameter of 10 to 2000 nanometers, ii) a length of 0.2 to 3 millimeters, iii) a specific surface area of ​​3 to 40 square meters per gram, and iv) a Canadian Standard Freeness of 0 to 100 milliliters; and b) 1 to 10 weight percent polyvinylpyrrolidone present as a coating on the surfaces of the fibers, which coating is not chemically or electrostatically bonded to the fibers, based on the total weight of the paper; wherein the paper has a thickness of 10 to 40 micrometers and a tensile strength of at least 15 megapascals.

[0008] The present invention relates to an electrochemical cell or electrochemical cell module comprising paper as an electrolyte separator or as a thermal or flame barrier, the paper comprising: a) 90 to 99 weight percent aramid fiber pulp, based on the total weight of the paper, the aramid fiber pulp comprising aramid polymer fibrils, the aramid polymer fibrils having i) a diameter of 10 to 2000 nanometers, ii) a length of 0.2 to 3 millimeters, iii) a specific surface area of ​​3 to 40 square meters per gram, and iv) a Canadian Standard Freeness of 0 to 100 milliliters; and b) 1 to 10 weight percent polyvinylpyrrolidone present as a coating on the surfaces of the fibers, which coating is not chemically or electrostatically bonded to the fibers, based on the total weight of the paper; Includes The invention further relates to an electrochemical cell or electrochemical cell module, wherein the paper has a thickness of 10 to 40 micrometers and a tensile strength of at least 15 megapascals or more. [Brief description of the drawings]

[0009] [Figure 1] Digital photograph of polyphenylene terephthalamide (PPD-T) / polyvinylpyrrolidone (PVP) fibrils. [Diagram 2] This is the designation for commercially available PPD-T pulp. [Diagram 3] 1 is a graphical representation comparing the distribution of pores in PPD-T / PVP filaments versus PPD-T filaments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] While the present invention can be embodied in various forms, the following description of some embodiments is made with the understanding that the present disclosure should be considered as an illustration of the present invention and is not intended to limit the present invention to the specific embodiments illustrated. Headings are provided for convenience only and should not be construed as limiting the present invention in any way. An embodiment illustrated in any heading or any portion of this disclosure may be combined with an embodiment illustrated in the same or any other heading or other portion of this disclosure.

[0011] Any combination of the elements described herein in all possible variations thereof is encompassed by the invention unless otherwise indicated herein or otherwise clearly contradicted by context.

[0012] definition As used herein, the term "paper" is used in its ordinary sense to refer to a nonwoven sheet prepared using conventional wet-laid papermaking processes and equipment. In the context of this disclosure, paper is also referred to interchangeably as "base paper." Unless otherwise specified herein, both the terms "paper" and "base paper" are deemed to include polyvinylpyrrolidone (PVP) coatings.

[0013] The "friction paper" referred to herein is a composite comprising the base paper described above and further comprising a friction resin coating different from the PVP coating.

[0014] "Pulp", with respect to use in friction paper, means particles of aramid material having stalks and fibrils extending therefrom, the stalks being generally columnar and about 10-50 microns in diameter, and the fibrils being merely a fraction or a few microns in diameter and hair-like members attached to the stalks and about 10-100 microns in length. In papermaking, the fibrils on the pulp are important because they act as hooks or fasteners to hold adjacent particles in the paper and provide integrity to the paper structure. As used herein, pulp has a surface area of ​​0.5 to 20 square meters per gram. Aramid pulp may be made, for example, by refining aramid floc or as described in U.S. Pat. No. 5,202,184.

[0015] Floc generally comprises staple fibers made by cutting continuous filament fibers into short lengths without significant fibrillation. The length of the staple fibers can be almost any length, but one suitable range is 1 mm to 12 mm for reinforcing fibers and 5 mm to 800 mm for staple fibers that are spun into yarns. Typically, floc has a surface area of ​​about 0.08 to 0.6 square meters per gram. Staple fibers suitable for use in the present invention are the reinforcing fibers disclosed in U.S. Patent No. 5,474,842 to Hoiness.

[0016] The term "fibrids" as used herein means very finely divided polymeric products of small, very thin, essentially two-dimensional particles having lengths and widths of about 100-1000 micrometers and thicknesses of about 0.1-1 micrometers.

[0017] In the context of this application, the term aramid includes polymers in which at least 85% of the amide (--CONH--) bonds are directly attached to two aromatic rings. It has been found that additives can be used with aramid; up to 10 weight percent of other polymeric materials can be blended with aramid, or copolymers can be used with as much as 10% of other diamines substituted for the diamines of the aramid, or as much as 10% of other diacid chlorides substituted for the diacid chlorides of the aramid. Para-aramid is an exemplary polymer in the fibers of the present invention, and poly(p-phenylene terephthalamide) (PPD-T) is the preferred para-aramid. Another suitable aramid type fiber is based on aromatic copolyamides, such as those prepared by the reaction of terephthaloyl chloride (TPA) with a combination mixture (e.g., 50 / 50 molar ratio) of p-phenylenediamine (PPD) and 3,4'-diaminodiphenyl ether (DPE). Yet another suitable fiber is that formed by the polycondensation reaction of two diamines, p-phenylenediamine and 5-amino-2-(p-aminophenyl)benzimidazole, with terephthalic acid or anhydride or their acid chloride derivatives, or isomers of the foregoing. Another fiber type is an aromatic copolymer derived from the copolymerization of para-phenylenediamine, 5(6)-amino-2-(p-aminophenyl)benzimidazole, and terephthaloyl dichloride.

[0018] paper In the context of this disclosure, paper is also referred to as base paper.

[0019] In one embodiment, the paper comprises 60 to 99 weight percent aramid fiber pulp, e.g., p-aramid fiber pulp, the pulp comprising fibers and a 1 to 40 weight percent polyvinylpyrrolidone (PVP) coating on the surfaces of the fibers, the coating being neither chemically nor electrostatically bonded to the fibers.

[0020] In another embodiment, the paper comprises 80 to 98 weight percent aramid fiber pulp, such as p-aramid fiber pulp, and 2 to 20 weight percent polyvinylpyrrolidone (PVP) coating.

[0021] In another embodiment, the paper comprises 80 to 95 weight percent aramid fiber pulp, such as p-aramid fiber pulp, and 5 to 20 weight percent polyvinylpyrrolidone (PVP) coating.

[0022] In a further embodiment, the paper comprises 80 to 90 weight percent aramid fiber pulp, such as p-aramid fiber pulp, and 10 to 20 weight percent polyvinylpyrrolidone (PVP) coating.

[0023] In yet another embodiment, the paper further comprises 1 to 30 weight percent aramid floc, such as p-aramid floc. Alternatively, the paper further comprises 1 to 20 weight percent aramid floc, such as p-aramid floc, or 1 to 10 weight percent aramid floc, such as p-aramid floc.

[0024] Paper can also be made using a combination of aramid floc and aramid fibrids, where the fibrids help hold the floc and other paper components together.

[0025] The paper may further include components such as fillers or friction modifying particles. Exemplary fillers include silica, diatomaceous earth, graphite, and alumina. Exemplary friction modifying particles include metal oxides, nitrides, carbides, and mixtures thereof. The friction modifying particles may have at least one dimension less than 1 micrometer.

[0026] One method of applying PVP to aramid pulp is by adding the PVP to an aqueous slurry of pulp and other fibrous material, forming a paper, and drying the paper, however other methods may also be used.

[0027] The paper may be made on any suitable paper machine using techniques well known in the art.

[0028] friction paper Friction paper as described herein is a composite that includes a base paper, as described above, and a resin coating.

[0029] In one embodiment, the friction paper comprises 40 to 95 percent by weight of base paper and 5 to 60 percent by weight of resin.

[0030] In another embodiment, the friction paper comprises 60 to 90 percent by weight of base paper and 10 to 40 percent by weight of resin.

[0031] friction paper resin The resin component of the friction paper may be a phenolic resin, a modified phenolic resin, a silicone, a polyimide, or a combination thereof.

[0032] Silicone resins useful in the present invention include, for example, heat curable silicone sealants and silicone rubbers. Another useful resin is an epoxy-modified phenolic resin, which contains about 5 to about 25 weight percent, preferably about 10 to about 15 weight percent, of an epoxy compound, with the remainder (excluding solvents and other processing aids) being the phenolic resin.

[0033] The resin is impregnated onto and into the base paper, as known in the art, and then cured by heat and pressure to form the final shape of the friction paper. Conventional techniques such as dip coating and surface coating may be used to impregnate the paper.

[0034] Industrial Applications The present invention is useful as a high energy friction material for use with clutch plates, transmission bands, brake shoes, synchronizer rings, friction discs or system plates.

[0035] Some embodiments disclosed herein are set forth in the following paragraphs, and any combination of these paragraphs (or portions thereof) may be made to clarify the embodiments. For example, if a composition described in an embodiment can vary by an additional feature or claim element, it should be understood that other compositions described in other embodiments can also vary by that same additional feature or claim element. For example, paragraph 1a discloses an embodiment in which the aramid fiber pulp in the paper of paragraph 1 is p-aramid fiber pulp; similarly, for any other embodiment disclosing a paper or composite comprising (or consisting of, or consisting essentially of) aramid fiber pulp, there is another embodiment in which the paper or composite comprises (or consists of, or consists essentially of) p-aramid fiber pulp. In general, for any embodiment described herein with respect to a composition (e.g., paper or composite) that comprises, consists of, or consists essentially of aramid fiber pulp or aramid floc or aramid fibrids, there is another corresponding embodiment that comprises, consists of, or consists essentially of p-aramid fiber pulp or p-aramid floc or p-aramid fibrids. Furthermore, the methods described herein that use the compositions may also vary with variations in such compositions.

[0036] Item 1: A paper comprising 60 to 99 weight percent aramid fiber pulp based on the total weight of the paper, the fiber pulp comprising fibers and 1 to 40 weight percent polyvinylpyrrolidone based on the total weight of the paper present as a coating on the surfaces of the fibers, the coating being neither chemically nor electrostatically bonded to the fibers.

[0037] Item 1a: In an embodiment, the aramid fiber pulp in the paper described in item 1 is p-aramid fiber pulp.

[0038] Item 2: The paper according to item 1 or 1a, comprising 80 to 99 weight percent aramid fiber pulp or p-aramid fiber pulp, and 1 to 20 weight percent polyvinylpyrrolidone. In an embodiment, the paper according to item 1 or 1a comprises 80 to 98 weight percent aramid fiber pulp or p-aramid fiber pulp, and 2 to 20 weight percent polyvinylpyrrolidone.

[0039] Item 3: The paper according to item 1 or 1a, comprising 80 to 95 weight percent aramid fiber pulp or p-aramid fiber pulp, and 5 to 20 weight percent polyvinylpyrrolidone.

[0040] Item 4: The paper according to item 1 or 1a, comprising 80 to 90 weight percent aramid fiber pulp or p-aramid fiber pulp, and 10 to 20 weight percent polyvinylpyrrolidone.

[0041] Item 4a: In an embodiment, there is provided a paper comprising aramid fiber pulp or p-aramid fiber pulp, the fiber pulp comprising fibers and polyvinylpyrrolidone present as a coating on the surfaces of the fibers, the coating not being chemically or electrostatically bonded to the fibers; and a weight ratio of aramid fiber pulp or p-aramid fiber pulp to polyvinylpyrrolidone is 60:40 to 99:1; or 80:20 to 99:1; or 80:20 to 98:2; or 80:20 to 95:5; or 80:20 to 90:10.

[0042] Item 5: The paper of any one of items 1 to 4a, having a ratio of tensile strength to average Gurley Air Permeability 300cc value of at least 4.0 MPa / sec. In an embodiment, the ratio of tensile strength to average Gurley Air Permeability 300cc value is at least 4.3 MPa / sec.

[0043] Item 6: The paper according to item 1, consisting essentially of or consisting of 60 to 99 weight percent aramid fiber pulp and 1 to 40 weight percent polyvinylpyrrolidone.

[0044] Item 6a: The paper according to item 1, consisting essentially of or consisting of 80 to 98 weight percent aramid fiber pulp and 2 to 20 weight percent polyvinylpyrrolidone.

[0045] Item 6b: The paper according to item 1, consisting essentially of or consisting of 80 to 95 weight percent aramid fiber pulp and 5 to 20 weight percent polyvinylpyrrolidone.

[0046] Item 6c: The paper according to item 1, consisting essentially of or consisting of 80 to 90 weight percent p-aramid fiber pulp and 10 to 20 weight percent polyvinylpyrrolidone.

[0047] Item 7: The paper of item 1 further comprising aramid floc, e.g., p-aramid floc, the floc comprising fibers, the floc being present in an amount of 1 to 30 weight percent based on the total weight of the paper, wherein the polyvinylpyrrolidone is present as a coating on the surfaces of the aramid fiber pulp and the aramid floc fibers, and the aramid fiber pulp is 98 weight percent or less based on the total weight of the paper. In an embodiment, the aramid fiber pulp and the aramid floc are p-aramid fiber pulp and p-aramid floc.

[0048] Item 7a: The paper of item 1 further comprising aramid floc, the floc comprising fibers, the floc being present in an amount of 1 to 20, or 5 to 20 weight percent based on the total weight of the paper, wherein the polyvinylpyrrolidone is present as a coating on the surfaces of the aramid fiber pulp fibers and the aramid floc fibers, and the p-aramid fiber pulp is 98 weight percent or less based on the total weight of the paper. In an embodiment, the aramid fiber pulp and the aramid floc are p-aramid fiber pulp and p-aramid floc.

[0049] Clause 7b: In an embodiment, there is provided a paper according to clause 4a, further comprising aramid floc. In one such embodiment, the aramid floc is present in an amount of 1 to 30, or 1 to 20, or 5 to 20 weight percent based on the total weight of the paper. In an embodiment, the aramid floc is p-aramid floc.

[0050] Item 8: The paper according to item 1, further comprising a combination of aramid floc and aramid fibrids, the aramid floc and aramid fibrids comprising fibers, the combination of aramid floc and aramid fibrids being present in an amount of 1 to 30, or 1 to 20, or 5 to 20 weight percent based on the total weight of the paper, wherein the polyvinylpyrrolidone is present as a coating on the surfaces of the aramid fiber pulp fibers and the aramid floc fibers and the aramid fibrids, and the aramid fiber pulp is 98 weight percent or less based on the total weight of the paper. In an embodiment, the aramid fiber pulp and the aramid floc and the aramid fibrids are p-aramid fiber pulp and p-aramid floc and p-aramid fibrids.

[0051] Clause 8a: In some embodiments, the paper according to clause 4a further comprises a combination of aramid floc and aramid fibrids. In one such embodiment, the combination of aramid floc and aramid fibrids is present in an amount of 1 to 30, or 1 to 20, or 5 to 20 weight percent based on the total weight of the paper. In an embodiment, the aramid fiber pulp and aramid floc and aramid fibrids are p-aramid fiber pulp and p-aramid floc and p-aramid fibrids.

[0052] Item 9: The paper according to any one of items 1 to 8a, further comprising a filler or friction modifying particles.

[0053] Item 10: The paper of item 9, wherein the filler or friction modifying particles are one or more of silica, diatomaceous earth, graphite, alumina, metal oxides, metal nitrides, or metal carbides.

[0054] Item 10a: The paper according to item 9, wherein the filler is one or more of silica, diatomaceous earth, graphite, or alumina.

[0055] Item 10b: The paper of item 9, wherein the friction modifying particles are one or more of a metal oxide, a metal nitride, or a metal carbide.

[0056] Item 11: The paper of item 7, consisting or consisting essentially of 60 to 98 weight percent aramid fiber pulp, based on the total weight of the paper, 1 to 30 weight percent aramid floc, based on the total weight of the paper, and 1 to 20 weight percent polyvinylpyrrolidone, based on the total weight of the paper. In an embodiment, the aramid fiber pulp and aramid floc are p-aramid fiber pulp and p-aramid floc.

[0057] Item 11a: The paper of item 7 consisting or consisting essentially of 60 to 93 weight percent aramid fiber pulp, based on the total weight of the paper, 5 to 20 weight percent aramid floc, based on the total weight of the paper, and 2 to 20 weight percent polyvinylpyrrolidone, based on the total weight of the paper. In an embodiment, the aramid fiber pulp and aramid floc are p-aramid fiber pulp and p-aramid floc.

[0058] Item 12: A composite comprising 40 to 95 weight percent of the paper according to item 1 and 5 to 60 weight percent of a resin, wherein the resin is a phenolic resin, a silicone, a polyimide, or a combination thereof.

[0059] Item 13: The composite according to item 12, comprising 60 to 90 weight percent of the paper according to item 1 and 10 to 40 weight percent of a resin.

[0060] Item 14: A composite comprising 40 to 95 weight percent of the paper according to item 7 and 5 to 60 weight percent of a resin, wherein the resin is a phenolic resin, a silicone, a polyimide, or a combination thereof.

[0061] Item 15: The composite according to item 14, comprising 60 to 90 weight percent of the paper according to item 7 and 10 to 40 weight percent of a resin.

[0062] In some embodiments, the present invention further relates to papers suitable for use in or with electrochemical cells; i.e., for example, as electrolyte separators or as thermal insulation or fire barriers for use inside or outside a cell or cell module. Paper electrolyte separators are useful for separating the cathode from the anode in an electrochemical cell; the paper also has suitable permeability for the electrolyte used in such cells. With the continued development of more powerful electrochemical cells (or commonly known as batteries), there is an increasing need for papers suitable as separators (commonly known as battery separators) that can operate at very high temperatures, or that can be used as thermal insulation or fire barriers in or around an electrochemical cell or an electrochemical module that includes multiple electrochemical cells. The terms "electrochemical cell" and "battery" are used interchangeably herein.

[0063] One of the requirements for a paper suitable for use as a separator in an electrochemical cell is that the paper be very thin. Many papers that are made very thin and are considered suitable for use as a separator in an electrochemical cell do not perform well in this application. In particular, very thin papers may not be strong enough for this application. Thus, there is a need for papers that have sufficient tensile strength and also have other properties suitable for use with electrochemical cells, such as porosity, high heat resistance, fire and flame resistance, etc.

[0064] It has been found that highly useful papers suitable for such electrochemical cell applications can be made from aramid fiber pulp containing aramid polymer fibrils further coated with a minimal amount of polyvinylpyrrolidone (PVP) on the surface of the fibrils. The strength of these coated papers has been found to be unexpectedly high in tensile strength when compared to papers containing aramid fiber pulp consisting of aramid polymer fibrils. One particularly useful embodiment of this paper is a paper containing aramid polymer fibrils made from a mixture of PPD-T / PVP polymers further coated with a minimal amount of polyvinylpyrrolidone (PVP) on the surface of those PPD-T / PVP fibrils.

[0065] Thus, in some embodiments, the present invention provides a paper suitable for use as a separator in an electrochemical cell, or as a thermal or flame barrier, comprising: a) 90 to 99 weight percent aramid fiber pulp based on the total weight of the paper, the aramid fiber pulp comprising aramid polymer fibrils, the aramid polymer fibrils comprising: i) a diameter of 10 to 2000 nanometers; ii) a length between 0.2 and 3 mm; iii) a specific surface area of ​​3 to 40 square meters per gram; and iv) Canadian Standard Freeness from 0 to 100 milliliters Aramid fiber pulp having the formula: b) 1 to 10 weight percent polyvinylpyrrolidone, based on the total weight of the paper, the polyvinylpyrrolidone being present as a coating on the surfaces of the fibers. Including, The paper has a thickness of 10 to 40 micrometers and a tensile strength of at least 15 megapascals or more. In some embodiments, the coating is not chemically or electrostatically bonded to the fibers.

[0066] A paper suitable for use as an electrochemical cell separator or as a thermal insulator comprises 90-99 weight percent aramid fiber pulp containing aramid polymer fibrils and 1-10 weight percent polyvinylpyrrolidone (PVP) coating on the surfaces of the fibers, preferably the paper comprises 90-97.5 weight percent aramid fiber pulp containing aramid polymers and 2.5-10 weight percent polyvinylpyrrolidone (PVP) coating on the surfaces of the fibers.

[0067] In some preferred embodiments, the aramid fiber pulp consists solely of aramid polymer fibrils. In some embodiments, the aramid fiber pulp either comprises or consists of aramid polymer fibrils, and the paper has aramid fibrids as a binder. The paper of any of these embodiments can further comprise aramid floc, if desired.

[0068] One method of applying a PVP coating to aramid fiber pulp is to add PVP to an aqueous slurry of pulp and other fibrous materials: i.e., the paper machine feed, followed by forming the paper and drying the paper, although papers suitable for use as separators or insulators for electrochemical cells can be made by other methods, if desired. Other methods, such as spraying after or during the papermaking process, kiss rolling, etc., can also be used. The amount of PVP applied to the paper is very small, with the paper having a final amount of PVP coating on the paper of about 10 weight percent or less; therefore, spraying the formed paper with an aqueous PVP solution prior to drying or calendering can make application of the PVP coating more convenient. However, it is believed that an improvement can be achieved by spraying the dried paper with a PVP solution followed by redrying.

[0069] Generally, very dilute aqueous solutions of PVP are suitable for spraying PVP coatings onto uncoated paper. One method for making a sprayable PVP solution is to add PVP powder to water at room temperature and stir for 5 minutes to completely dissolve the powder in the water. Desirable and suitable sprayable PVP solutions include about 2.5 to 15 weight percent PVP in water, although higher or lower concentrations of PVP may be used depending on the application process. Excess water is then removed by applying to the paper and then heating or drying the paper.

[0070] In a preferred embodiment, the aramid fiber pulp in the paper is greater than 90% by weight of aramid polymer fibrids that are mechanically bound in the paper. If desired, optional binders of aramid polymer fibrids can be used; if used, they are present in the paper in amounts of 5 weight percent or less. This uncoated paper can be essentially handled as any other paper and has measurable tensile strength and mechanical properties. Again, in a preferred embodiment, the paper further comprises a coating of PVP, 1 to 10 weight percent based on the weight of the paper. Due to the nanofiber structure of the fibrils, when the paper is coated by spraying PVP on one surface of the paper, the PVP provides a small amount of permeable coating on the fibrils and provides some binding points between the fibrils, but does not appreciably affect the permeability of the sheet to electrolytes. In other words, the aramid polymer fibrids are the primary binder in the paper, and the PVP provides the secondary binding.

[0071] In some preferred embodiments, the paper has both PVP present in the aramid polymer fibrils and as a polymer coating on the fibrils. It is believed that the amount of PVP in the fibrils and the amount in the coating can be determined separately, with the amount in the coating being found by carefully washing the paper to remove the water-soluble PVP coating and then analyzing the washings for the presence of PVP. The remaining uncoated paper can then be analyzed by methods such as TGA to determine the amount of PVP in the aramid polymer fibrils in the base paper. It is believed that the PVP present in the fibrils is substantially alloyed with the PPD-T polymer and is substantially not removable by washing with water.

[0072] Generally, the mechanical strength increase imparted to paper by application of only a small PVP coating is nearly double that of uncoated paper. For example, a final coating of about 2 weight percent PVP on the paper can increase the tensile strength of the paper by more than 100%, and a final coating of about 4 weight percent PVP on the paper can increase the tensile strength of the paper by more than 150%. Surprisingly, the small amount of PVP coating on the paper means that the paper remains porous enough for use in electrochemical cell applications.

[0073] The term "aramid polymer fibrils" as used herein refers to hairy fibrous material having a diameter of 10 to 2000 nanometers, preferably 10 to 1200 nanometers, made from aramid polymers or polymer blends containing at least two polymers in which a majority (greater than 50 weight percent) of aramid polymer is present. FIG. 1 is a representative digital photograph of an aramid polymer fibril. The aramid polymer fibrils further have a preferred length of 0.2 to 3 millimeters. The "length" of fibrous materials referred to herein, such as aramid polymer fibrils and pulp, is meant to be the measured "length-weighted average" length. In some preferred embodiments, the aramid polymer fibrils are refined aramid polymer fibrils made from floc by subjecting the floc to a refining process that shears the floc into smaller aramid polymer fibrils. In some preferred embodiments, the aramid polymer fibrils have a length of 0.4 to 3 millimeters (mm), preferably 0.8 to 3 mm.

[0074] It is believed that the diameter of the aramid polymer fibrils affects the pore size of the paper, and that aramid polymer fibrils with a diameter of more than 2000 nanometers create paper with undesirably high pore size, which may ultimately lead to paper failure.Also, it is believed that aramid polymer fibrils with a diameter of less than 10 nanometers or a length of less than about 0.2 millimeters do not contribute to the mechanical strength of the paper, so it is desirable for the majority of the aramid polymer fibrils to have a length of 0.2 millimeters or more.Furthermore, the small diameter of the aramid polymer fibrils facilitates the use of the fibrous material in very thin papers.

[0075] Additionally, the aramid polymer fibrils have an aspect ratio that may range from about 150 to 300,000. Aspect ratio is also known as length divided by diameter, and the phrases "aspect ratio", "average length-to-diameter ratio" and "length-to-diameter" are used interchangeably herein. In some embodiments, the average length-to-diameter ratio of the aramid polymer fibrils is greater than or equal to about 1000. In some embodiments, the aramid polymer fibrils have an average length-to-diameter ratio of less than or equal to about 3000. In some preferred embodiments, the average length-to-diameter ratio ranges from about 1000 to 3000. It is believed that the higher average length-to-diameter ratio of the aramid polymer fibrils contributes to better mechanical reinforcement and therefore better mechanical properties of the paper.

[0076] Because a qualitative measurement of certain fiber materials, such as aramid polymer fibrils, can be difficult, such fiber materials can be compared by measuring the "freeness" of the fiber materials. The most common techniques for measuring freeness measure either the Canadian Standard Freeness (CSF) or the Shopper-Rigler Freeness (SRF).

[0077] The inventors believe that Canadian Standard Freeness (CSF) is the preferred technique for characterizing aramid polymer fibrils for use herein. Aramid polymer fibrils are preferably produced by refining aramid polymer fibers or flocs to produce fibrils. Such fibrils preferably have a CSF of 0-50 milliliters, and in some embodiments, a CSF of 0-20 milliliters. CSF is one measure of the fineness of the aramid polymer fibrils or the degree to which they are fibrillated during refining, with very fine aramid polymer fibrils having very low CSF. Also, materials with a wide size distribution generally have high CSF values, so a low CSF value indicates uniformly sized fibrils.

[0078] Aramid polymer fibrils as defined herein are fibrous materials and are quite different from conventional aramid polymer pulps of the prior art. Such aramid polymer pulps may be preferably produced by refining flocs or directly from the ingredients taught in US Pat. Nos. 5,202,184, 5,523,034, and 5,532,034. However, such methods not only provide fibrous materials with a wider range of fiber sizes and lengths due to the difficulty of controlling such methods, but also provide both "stalks" and fibrils extending from the stalks, the stalks being roughly columnar remnants of the original aramid polymer flocs and having diameters of about 10 to 50 microns. Furthermore, for conventional aramid polymer pulps, the length measurement is understood to be the characteristic length of the pulp's stalks, also called "pulp stalks".

[0079] Also, the average length to diameter ratio of aramid polymer fibrils suitable for use as separators or insulators in electrochemical cells is much greater than the average length to diameter ratio of conventional aramid polymer pulps, such as those made by the processes of U.S. Pat. Nos. 5,084,136, 5,171,402, and 8,211,272, which are believed to have average length to diameter ratios generally less than 150, or the average length to diameter ratio of highly refined pulps, such as those disclosed in U.S. Patent Application Publication Nos. 2016 / 0362525 and 2017 / 0204258, which are believed to be less than the average length to diameter ratio of conventional pulps (e.g., generally less than 100).

[0080] Fibrils with a higher average length to diameter ratio are believed to contribute to better paper barrier properties including lower / smaller pore size and higher Gurley Hill porosity along with higher paper tensile strength.

[0081] Additionally, the aramid polymer fibrils are essentially free of stalk or stalk-free aramid polymer fibrils. As used herein, the term "stalk-free aramid polymer fibrils" means that at least 95% by weight of the fiber material are aramid polymer fibrils having a desired diameter of 10 to 2000 nanometers as determined by optical measurement of a fibril sample using 500x or 1000x magnification. In some embodiments, at least 98% by weight of the fiber material are aramid polymer fibrils having a desired diameter of 10 to 2000 nanometers as determined by optical measurement of a fibril sample using 500x or 1000x magnification. In some embodiments, 100% by weight of the fiber material are aramid polymer fibrils having a desired diameter of 10 to 2000 nanometers as determined by optical measurement of a fibril sample using 500x or 1000x magnification.

[0082] One preferred method of producing stalk-free aramid polymer fibrils is to refine fibers or flocs made from a polymer blend containing at least two polymers with a majority (greater than 50 weight percent) of the aramid polymer being present. One preferred polymer blend is a polymer blend of 80-96 weight percent polyparaphenylene terephthalamide (PPD-T) and 4-20 weight percent polyvinylpyrrolidone (PVP). When aramid fibers or aramid flocs made from this PPD-T / PVP polymer blend are refined, the resulting fiber material is essentially all fibrils with essentially no larger stalks present in the material, as shown in the digital photograph of FIG. 1. It is believed that at least 4 weight percent PVP must be present in the fiber or floc for the original fiber or floc to be refined into fibrils with essentially no stalk remaining. This is in comparison to conventional refined aramid pulp made from polyparaphenylene terephthalamide (PPD-T) homopolymer, shown in FIG. 2, which has visible stalks.

[0083] The porosity and crystallinity of filaments made from blends of 80-96 weight percent PPD-T and 4-20 weight percent PVP have been found to be dramatically different from filaments consisting of PPD-T alone. The term "fiber" is used interchangeably with the term "filament" herein. Fibers spun directly onto bobbins from a polymer solution without cutting are commonly referred to as continuous fibers or filaments, and multifilament yarns contain multiple continuous filaments.

[0084] FIG. 3 illustrates the difference in x-ray scattering for the two types of filaments. Curve 20 represents a filament of the PPD-T / PVP blend, and curve 30 represents a filament made with PPD-T alone. Curve 30 illustrates that the PPD-T filament has a significant peak centered at about 2 Angstroms (and a much smaller peak centered at 4 Angstroms), indicating very small pores in the fiber. Curve 20 illustrates that the pore size distribution for the PPD-T / PVP blend is much broader, with a peak centered at about 3 Angstroms and a very broad sloping peak centered at about 250 Angstroms, but extending over a region ranging from about 70 to 600 Angstroms. This is believed to indicate that the filament made from the PPD-T / PVP blend has a significantly greater number of pores that are much larger than the PPD-T filament.

[0085] Moreover, due to this difference in the crystallinity and pore structure of the fibers, as illustrated in Figure 1, it is believed that mechanically refining the filaments results in much finer and more uniformly distributed fibrils. In other words, the very high crystallinity and low porosity of the PPD-T fibers means that when mechanically refined, the refining shear action mainly abrades the surface of the filaments to produce the typical fibrillated stalk structure (as shown in Figure 2), whereas the low crystallinity and high porosity of the PPD-T / PVP blend filaments means that they can be easily separated into individual refined fibrils under the same shear action, with a large number of fibrils of smaller and relatively more uniform diameter, and more importantly, essentially free of any stalks (i.e., no stalks). The aramid polymer fibrils are believed to have a relatively uniform diameter with a total diameter size range of about 300 nanometers as visually measured from SEM micrographs.

[0086] Aramid polymer fibrils are preferably produced from aramid floc having PPD-T as the majority polymeric material component by weight and at least one other polymeric material component, which components are preferably mutually immiscible such that at least two polymeric materials are present in the floc as well-mixed but separate solid phases. Such aramid floc, when refined, produces aramid polymer fibrils having domains of two different polymeric materials, one phase being a continuous or primary polymer phase or PPD-T polymer and the other phase being a discontinuous or secondary polymer phase, which in the preferred case is a PVP polymer.

[0087] The discontinuous or secondary polymer phase is believed to exist as small nanometer-sized crystalline domains of material that pass through the floc and act as break points in the floc structure during the refining process, facilitating faster and more complete refining of the floc to form fibrils. After refining, a portion of the discontinuous or secondary polymer from each break point is present on or at the surface of each fibril resulting from the refining process.

[0088] Aramid polymer fibrils also have a high surface area. The terms "surface area," "specific surface area," and "BET surface area" are used interchangeably herein. Aramid polymer fibrils have a surface area of ​​about 3 to 40 m. 2 In some embodiments, the specific surface area is 6 m 2 / g or more, and in some embodiments the specific surface area is 8 m 2 / g or more. One particularly preferred range of the specific surface area is 6 to 20 m 2 / g.

[0089] In comparison, conventional pulp refined from floe made from a single polymeric material or from a miscible blend of polymeric materials that does not have discrete secondary polymer domains would not have such a high surface area. Moreover, if the floe were refined sufficiently to have such a high measured surface area, the resulting pulp particles would have such a low aspect ratio (resulting from a very low average length) that they would not provide adequate strength.

[0090] The preferred aramid fibrils contain 80 to 96 weight percent poly(paraphenylene terephthalamide) (also known and used herein as polyparaphenylene terephthalamide or PPD-T). By PPD-T is meant the homopolymer resulting from the mole-for-mole polymerization of p-phenylenediamine and terephthaloyl chloride, and also the copolymer resulting from the incorporation of small amounts of other diamines and small amounts of other diacid chlorides along with p-phenylenediamine and terephthaloyl chloride. Typically, the other diamines and other diacid chlorides can be used in amounts up to about 10 mole percent of the p-phenylenediamine or terephthaloyl chloride, or perhaps slightly higher, provided only that the other diamines and diacid chlorides do not have reactive groups that will interfere with the polymerization reaction. PPD-T also refers to copolymers obtained from the incorporation of other aromatic diamines and other aromatic diacid chlorides, such as 2,6-naphthaloyl chloride or chloro- or dichloro-terephthaloyl chloride, provided only that the other aromatic diamines and aromatic diacid chlorides are present in amounts that allow the preparation of anisotropic spinning dopes. The preparation of PPD-T is described in U.S. Pat. Nos. 3,869,429, 4,308,374 and 4,698,414.

[0091] The preferred aramid fibrils also contain 4 to 20 weight percent poly(vinylpyrrolidone) (also known and used herein as polyvinylpyrrolidone or PVP). By PVP is meant a polymer resulting from the linear polymerization of monomer units of N-vinyl-2-pyrrolidone and containing small amounts of comonomers that may be present at concentrations below those that do not interfere with the interaction of the PVP with the PPD-T. PVPs with molecular weights ranging from about 5000 to about 1,000,000 can be used. Very high molecular weight PVPs produce high viscosity spin dopes. PVPs with molecular weights of about 10,000 to about 360,000 are preferred.

[0092] Aramid polymer fibrils are preferably made by solution spinning continuous filament yarns from a dope containing an aramid polymer, cutting the continuous filament yarns into flocs, and then mechanically refining the flocs into fibrils using one or more refiners. In a preferred method, the dope is a solution containing a combination of PPD-T and PVP polymers in sulfuric acid. Examples of representative processes for making continuous filament yarns can be found in U.S. Pat. Nos. 5,073,440 and 5,094,913 and U.S. Patent Application Publication No. 2006 / 0113700. The aramid flocs are then cut from the continuous filament yarns. Aramid flocs before refining generally have a length of about 2 millimeters to about 25.4 millimeters, sometimes 2 to 10 millimeters or even 3 to 10 millimeters.

[0093] Aramid polymer fibrils are preferably produced from the floc by refining or fibrillating the PPD-T / PVP floc using techniques that cut, pulp, or grind the floc using mechanical methods that are convenient for paper, such as dry and wet disk or cone refining, hydrapulping, and beating. Refining is preferably performed on a dispersion of the floc in water, and preferably the dispersion is refined by multiple passes through a refiner, i.e., the refined dispersion leaving the refiner is recycled through the same or a second refiner for a second pass through the refiner, etc. The starting dispersion generally has a solids content of about 1-4 percent by weight of the floc in water. The starting floc preferably has a length of about 3-25.4 millimeters (0.125-1 inch).

[0094] If the floc is a PPD-T / PVP floc, it may be completely fibrillated into stalk-free aramid polymer fibrils after just three passes through the refiner and is then suitable for making paper. The stalk-free aramid polymer fibrils have a very low Canadian Standard Freeness (CSF) compared to pulps made from fibers that tend to fibrillate to form mixtures containing large amounts of stalk combined with the fibrils. Suitable fibrils are obtained with three passes through the refiner, although further passes through the refiner are possible and as many as 20 or more passes are believed to be helpful in further dispersing and homogenizing the fibrils, provided that they are not detrimental to the final strength of the paper. Preferably, the fibrils are made by recirculating the dispersion through the refiner for 3 to 20 passes, with some embodiments using 3 to 10 passes through the refiner.

[0095] Once refined, the fibril-water mixture can be used directly as a feed for the paper machine, or water can be added to or removed from the mixture before it is used as a feed for the paper machine. The fibril-water mixture can be combined with a slurry of the refined fibril-water mixture to prepare a feed containing both fibrils and fibrids as a fibrous material for use in the paper machine. Due to the high surface area of ​​the fibrils, the consistency of the papermaking feed is similar to that of a thick, highly viscous flour-water mixture, similar to a gel. In general, to make suitable paper, the aqueous feed should have less than 5 weight percent, preferably less than about 0.05 weight percent, of fibrous material. Higher amounts of fibrous material are considered to be too viscous for suitable paper. In some embodiments, the aqueous feed should have less than 5 weight percent fibrils, preferably less than about 0.05 weight percent fibrils. If desired, an additional PVP coating can be added to the feed.

[0096] The fibrous material in water is converted into paper in a suitable papermaking device capable of producing very thin paper. Representative devices include, but are not limited to, continuous processes such as Fourdrinier or inclined wire machines, or batch processes such as hand-made papermaking in handsheet molds including forming screens. For a general process of forming aramid materials into paper, reference can be made to U.S. Patent No. 3,756,908 to Gross and U.S. Patent No. 5,026,456 to Hesler et al.

[0097] Specifically, a commercially suitable process for making paper on a paper machine can include feeding an aqueous dispersion of fibrous material containing fibrils and optionally fibrids and other fibrous material in the desired amounts and ratios to the headbox of a paper machine, then uniformly wet-laying and dispersing these solids as a web on a papermaking wire to remove most of the liquid water. The wet web can then be dried on a dryer drum to form paper. Preferably, the paper is then further calendered or pressed under pressure and heat in the nip of a hot roll calender or by other means to consolidate and densify the paper into a layer having the desired thickness and properties.

[0098] It is believed that, with sufficient care, stalk-free aramid polymer fibrils can be obtained from conventional PPD-T pulp if subsequent processes after the refining step are used to separate or recover the fibrils from the stalk. If such fibrils meet the definition of "stalk-free" as described herein, they are believed to be suitable fibrils for use in paper.

[0099] Papers suitable for use as separators or thermal or fire retardants in electrochemical cells can have a number of preferred properties. These may include a particular thickness range, a sufficient minimum tensile strength to be suitable for use in the manufacture of batteries, an appropriate mean flow pore size range, and other properties that provide value in use, such as flame retardancy. Flame retardant papers are particularly desirable.

[0100] The PVP coated paper preferably has a thickness of 10 to 50 micrometers. This thickness range is compatible with the typical space available in a battery for a paper separator. Paper thicknesses less than 10 micrometers are not considered to be strong enough to handle the battery manufacturing process, and paper thicknesses greater than 50 micrometers have limited application due to the limited space in a typical battery, and such thick paper also increases cost, which is undesirable. In some embodiments, the paper thickness is 15 micrometers or more, and in some embodiments, the paper thickness is 40 micrometers or less. One preferred paper thickness range is 15 to 40 micrometers.

[0101] PVP coated papers suitable for use in or with electrochemical cells have a tensile strength of at least 15 megapascals or greater. It is believed that the paper requires this level of tensile strength to withstand the battery manufacturing process, including the cell winding process (winding the separator with the current collector, anode, and cathode). The tensile strength also contributes to the dendrite barrier of the separator during use. In some embodiments, the paper preferably has a tensile strength of 50 megapascals or less. In some embodiments, the paper preferably has a tensile strength of 100 megapascals or less. Tensile strengths above this value do not have adverse effects, but the parameter reaches a point where the value is reduced. In some embodiments, the paper has a tensile strength of 15 to 50 megapascals. In some embodiments, the paper has a tensile strength of 15 to 100 megapascals.

[0102] In some embodiments, the PVP coated paper preferably has an average flow pore size of 0.01 to 0.5 micrometers. Paper with an average flow pore size in this range is believed to have good electrolyte absorption by capillary forces, thus low ionic resistance, and good barrier properties that can prevent internal short circuits caused by lithium metal dendrites. In some preferred embodiments, the paper has an average flow pore size of about 0.05 to 0.5 micrometers.

[0103] The inventors have also found that a single layer of paper containing PPD-T / PVP fibrils has surprisingly good flammability performance when tested in the Thermal Performance Protection Test (TPP). TPP is a measure of flammability performance against a combination of radiant and convective heat. Paper containing PPD-T / PVP fibrils was found to have better TPP performance than paper made with PPD-T floc only when normalized for thickness. That is, paper containing PPD-T / PVP fibrils was better based on thickness normalization than paper containing PPD-T floc, which is inherently flame retardant, even though the paper did not contain all aramid material and did contain PVP, which is in fact a flammable thermoplastic.

[0104] In some embodiments, the fibrous material in the paper is only fibrils. However, in some embodiments, the paper comprises 95-100 weight percent fibrils and 0-5 weight percent aramid fibrids, based on the total weight of fibrils and fibrids in the paper. In some embodiments, the paper comprises fibrils and fibrids, and the fibrils are present in an amount of 95 weight percent to less than 100 weight percent, based on the total weight of fibrils and fibrids in the paper.

[0105] Aramid fibrids, when present in paper, are used as binder materials. While fibrids are fibrous materials, fibrids are not fibers. The term "aramid fibrids" refers to non-granular, film-like particles of aromatic polyamides having a melting or decomposition point above 320°C. The average length of the fibrids is 0.2 to 1 mm, and the aspect ratio of the length to width is 5:1 to 10:1. The thickness dimension is on the order of a fraction of a micron. Such aramid fibrids can be used in a wet state before drying and can be deposited as a physically entangled binder in the flock component of paper. Fibrids can be prepared using fiberizers such as those disclosed in U.S. Pat. No. 3,018,091, in which a polymer solution is precipitated and sheared in a single step. A preferred aramid fibrid comprises poly(metaphenylene isophthalamide) polymer.

[0106] Poly(metaphenylene isophthalamide) (also known and used herein as polymetaphenylene isophthalamide or MPD-I) refers to homopolymers resulting from the mole-for-mole polymerization of m-phenylenediamine and isophthaloyl dichloride, and also copolymers resulting from the incorporation of small amounts of other diamines and diacid chlorides together with m-phenylenediamine. Usually, the other diamines and diacid chlorides can be used in amounts up to about 10 mole percent of m-phenylenediamine or isophthaloyl dichloride, provided only that the other diamines and diacid chlorides do not have reactive groups that interfere with the polymerization reaction. MPD-I also refers to copolymers resulting from the incorporation of other aromatic diamines and other aromatic diacid chlorides, provided only that the other aromatic diamines and diacid chlorides are present in amounts that do not allow the preparation of anisotropic spinning dopes. The preparation of MPD-I is described in US Pat. No. 3,063,966 and US Pat. No. 3,287,324.

[0107] The addition of fibrids to the paper increases the mechanical strength of the separator by binding the fibrils together, but the fibrids are also a good barrier to electrolyte transport, so their presence increases the ionic resistance.

[0108] PVP coated paper, which is particularly useful as a separator in lithium ion batteries, has a resistivity of about 10 ohm-cm 2 less than, advantageously about 1 ohm-cm 2 ~5 ohm-cm 2 In some embodiments, the paper separator has a MacMullin number of about 2 to 15, and in some embodiments, about 4 to about 13. In other embodiments, the MacMullin number is about 4 to about 10. The MacMullin number (Nm) is a dimensionless number that is a measure of the ionic resistance of the separator and is defined as the ratio of the resistivity of a separator sample filled with electrolyte to the resistivity of an equivalent amount of electrolyte alone.

[0109] In some other embodiments, the present invention provides an electrochemical cell comprising paper as an electrolyte separator or as a thermal or flame barrier, the paper comprising: a) 90 to 99 weight percent aramid fiber pulp based on the total weight of the paper, the aramid fiber pulp comprising aramid polymer fibrils, the aramid polymer fibrils comprising: i) a diameter of 10 to 2000 nanometers; ii) a length between 0.2 and 3 mm; iii) a specific surface area of ​​3 to 40 square meters per gram; and iv) Canadian Standard Freeness from 0 to 100 milliliters Aramid fiber pulp having the formula: b) 1 to 10 weight percent polyvinylpyrrolidone, based on the total weight of the paper, the polyvinylpyrrolidone being present as a coating on the surfaces of the fibers. Including, The paper has a thickness of 10 to 40 micrometers and a tensile strength of at least 15 megapascals or more. In some embodiments, the coating is not chemically or electrostatically bonded to the fibers.

[0110] The term "electrochemical cell" is used interchangeably with the term "battery" herein, and is further intended to include such things as capacitors and other devices having (1) a cathode, (2) an anode, (3) a physical separation device between the cathode and anode to help prevent short circuits, and (4) some type of electrolyte. In many applications, a battery separator is placed between the positive (cathode) and negative (anode) plates in a battery to provide structural separation between these electrodes of opposite charge and allow the electrolyte to assist in the passage of electrical current through the separator.

[0111] It is contemplated that the electrochemical cell may include paper as a thermal insulator or flame barrier, meaning that the paper may be used either internally or externally to the electrochemical cell. For example, paper may be used as a thermal insulator or flame barrier within the electrochemical cell, or may be used to insulate the electrochemical cell from other electrochemical cells. It is contemplated, but not limited to, that the use of paper as an external thermal insulator or flame barrier may be further extended to insulating a bank of electrochemical cells, or insulating an electrochemical cell module or battery module. Preferably, the paper is both a thermal insulator and a flame barrier, preventing or delaying hot spots in one electrochemical cell from affecting another electrochemical cell, and acting as a flame barrier between cells or battery modules in the unlikely event of a fire.

[0112] The properties, characteristics, and elements of paper used in electrochemical cells as electrolyte separators or as heat or flame insulation / barriers are the same as those of both uncoated and PVP coated papers previously described herein as suitable for such use. Furthermore, the inventors have also found that single-ply papers are useful as both heat and flame barriers. In particular, as previously described herein, the inventors have also found that single-ply papers containing PPD-T / PVP fibrils have surprisingly good flammability performance when tested in the Thermal Performance Protection Test (TPP). TPP is a measure of flammability performance against a combination of radiant and convective heat. Papers containing PPD-T / PVP fibrils have been found to have better TPP performance than papers made with only PPD-T floc when normalized for thickness. That is, the paper containing PPD-T / PVP fibrils outperformed the paper containing PPD-T floc, which is inherently flame retardant, on a normalized thickness basis, even though the paper did not contain all aramid material and did contain PVP, which is in fact a flammable thermoplastic.

[0113] The present invention is further defined in the following examples, in which all parts and percentages are by weight unless otherwise specified. It should be understood that these examples, while illustrating preferred embodiments of the present invention, are given by way of illustration only and should not be construed as limiting in any way. From the above discussion and these examples, one skilled in the art can ascertain the essential characteristics of the present invention, and can make various modifications and alterations to the present invention to suit various applications and conditions without departing from the spirit and scope thereof.

[0114] Test Method The following test methods were used in the examples below.

[0115] The average thickness of the base paper and the friction paper was measured according to ASTM D645M-97 (2007) using a Thwing-Albert ProGage instrument at five points on the paper samples.

[0116] The average thickness of the friction paper was measured by a thickness gauge, model ID-C1128 Mitsutoyo Corporation, and the thickness at the breaking point of the paper sample was used.

[0117] The thickness of papers suitable for use as separators or insulators in electrochemical cells was measured according to ASTM D374-99 and is reported in mils and converted to micrometers.

[0118] The basis weight of the base paper suitable for the friction paper and the friction paper was measured in accordance with ASTM D646-13.

[0119] The basis weight of the friction paper was calculated by the measured weight divided by the area (21 cm x 9 cm) immediately after curing.

[0120] The basis weight of papers suitable for use as separators or insulators in electrochemical cells is measured in g / m2 according to ASTM D 646-96. 2 reported.

[0121] The porosity and air permeability of the base paper and friction paper suitable for friction paper were measured according to ASTM D726-94 using a Genuine Gurley 4320 Gurley Densometer 4110 (Gurley Precision Instruments, Troy, NY). Individual samples were placed in the holder of the densometer, and air at a pressure of 0.304 (kPa) was pumped into 0.1 inch of the sample. 2 or 0.645 cm 2 Push through to an area of ​​1 inch 2 or 6.45 cm 2 The software will recalculate according to 300cc(cm 3 The time in seconds required for 1000 g of air to pass through the sample is referred to herein as the Gurley Air Permeability 300cc value (sec / 300 cm 3The measurements were recorded as Gurley Air Permeability with units of time (seconds or seconds / 300cc). Values ​​are reported as the average of five tests for each sample. The machine also calculates porosity. Qualitatively, porosity and permeability are related in that higher porosity results in higher permeability, although it should be noted that permeability is reported here by the time (in seconds) it takes for 300cc of air to pass through the sample. Less time equates to higher permeability, so time in seconds is actually inversely related to permeability.

[0122] The Gurley Hill porosity of papers suitable for use as separators or insulators in electrochemical cells was measured in accordance with TAPPI T460 om-96 as the air resistance in seconds per 100 milliliters of cylinder displacement over a circular area of ​​approximately 6.4 square centimeters of the paper using a pressure differential of 1.22 kPa.

[0123] The mean flow pore size of papers suitable for use as separators or insulators in electrochemical cells is measured according to ASTM designation E 1294-89 "Standard Test Method for Pore Size Characteristics of Membrane Filters Using Automated Liquid Porosimeter", which estimates the pore size characteristics of membranes having pore size diameters from 0.05 μm to 300 μm by using the automated bubble point method of ASTM designation F 316-03.

[0124] The bubble point of papers suitable for use as separators or insulators in electrochemical cells was measured according to ASTM F 316-03(2011). The maximum pore size bubble point test is performed by pre-wetting the filter, increasing the gas pressure upstream of the filter at a predetermined rate, and monitoring the downstream gas bubbles to indicate passage of gas through the largest diameter filter pore. The pressure required to blow out the first open bubble detectable by its rise through the layer of liquid covering the filter is called the "bubble point" and is used to calculate the maximum pore size.

[0125] The ionic resistivity of papers suitable for use as separators or insulators in electrochemical cells is measured in milliohm-cm according to ASTM D7148-13. 2 reported.

[0126] The porosity of papers suitable for use as separators or insulators in electrochemical cells was measured according to ASTM C830-00 and reported in percent (%).

[0127] The McMullin number (Nm) is a dimensionless number that is a measure of the ionic resistance of the separator and is defined as the ratio of the resistivity of a separator sample filled with electrolyte to the resistivity of an equivalent amount of electrolyte alone.

[0128] The tensile strength and elongation of papers suitable for use as separators or insulators in electrochemical cells were measured according to ASTM D 828-97 using 2.54 cm wide specimens and 18 cm gauge length and reported in N / cm.

[0129] The tensile strength values ​​of both the base paper suitable for the friction paper and the friction paper were measured according to ASTM D828-16. Values ​​are reported as the average of eight tests for each sample. EXAMPLES

[0130] The following examples are given to illustrate the invention and should not be construed as limiting it in any manner. All parts and percentages are by weight unless otherwise indicated. Examples prepared in accordance with the current invention are designated by a numerical value. Control or comparative examples are designated by a letter. Data and test results for the comparative and inventive examples are shown in Tables 1 and 2.

[0131] The pulp used in all examples was p-aramid Kevlar® merge 1F892 at 2.25 denier per filament, commercially available from EI DuPont de Nemours and Company, Wilmington, Del.

[0132] The floc was p-aramid Kevlar® merge 1F570 in 3 mm cut lengths, also commercially available from EI DuPont.

[0133] The PVP was obtained from BASF, Florham, NJ under the trade name Sokalan. The grade was K30P.

[0134] Preparation of Base Paper for Comparative Example A The p-aramid pulp was added to the water with stirring to obtain a 2% slurry of p-aramid pulp. The slurry was filtered through a filter bag and the wet filter cake was pressed at 100 psi pressure in a flat press at ambient temperature for 1 minute to complete the dewatering. The paper was not dried.

[0135] 7.46 g of p-aramid pulp was added to 2.5 liters of water to form a second slurry, which was then fed onto a filter screen in a laboratory paper machine. The formed paper was not pressed further and was dried at 300+ / -20°C for 5 minutes.

[0136] The dried paper had an average thickness of 0.72 mm and a thickness of 168 g / m 2 (gsm, grams per square meter), and a porosity of 83.8%. The paper was tested for air permeability and tensile strength, and the results are shown in Table 1.

[0137] Preparation of Base Paper for Example 1 This was prepared similarly to Comparative Example A, except that after the p-aramid pulp was added to make a slurry, an amount of PVP was added, also with stirring, in an amount such that the weight of PVP added was 5% of the weight of the p-aramid pulp added. The pressure, time and temperature were the same as for Comparative Example A.

[0138] The dried paper had an average thickness of 0.69 mm and a thickness of 170 g / m 2 and a porosity of 82.9%. The paper was tested for air permeability and tensile strength and the results are shown in Table 1.

[0139] Preparation of Base Paper for Example 2 It was prepared similarly to Comparative Example A, except that after the p-aramid pulp was added to make a slurry, an amount of p-aramid floe was added with stirring in an amount such that the weight of the p-aramid floe added was 20% of the weight of the p-aramid pulp added, and an amount of PVP was added, also with stirring, in an amount such that the weight of the PVP added was 5% of the weight of the p-aramid pulp added. The pressure, time and temperature were the same as for Comparative Example A.

[0140] The dried paper had an average thickness of 0.76 mm and a thickness of 164 g / m 2 and a porosity of 85.1%. The paper was tested for air permeability and tensile strength and the results are shown in Table 1.

[0141] [Table 1]

[0142] Preparation of friction paper To test the efficacy of the base paper as a friction material, the base paper was immersed in a phenolic resin. The resin was type PR54562 in methanol solvent (30% solution) from Sumitomo Bakelite, NA (Novi, MI, USA). After immersion, the paper was removed and excess resin was drained off. The paper was air dried for 30 minutes and then dried in an oven at 100°C for 15 minutes. The resin content of the paper was measured in percent concentration by mass. The paper was then placed between glass plates and the resin was cured at 165°C for 10 minutes, followed by curing in an oven at 165°C for 5 hours. The resin content in the coated paper was determined by comparing the relative weight of the paper before and after resin coating.

[0143] Comparative Example B was made from the base paper of Comparative Example A. Examples 3 to 8 were made similarly to Comparative Example B, except that PVP was added during the preparation of the base paper as described for Example 1 in the amounts shown in Table 2.

[0144] The physical properties, averaged over seven samples, were determined for each type of friction paper and are summarized in Table 2.

[0145] Tensile tests were performed on 120x10mm test samples of friction paper at a chuck distance of 60mm. Thickness was measured at three points along the sample and the thickness closest to the break was used for calculations. Tests were performed at ambient temperature (approximately 23°C) at a speed of 1mm per minute. The highest and lowest tensile values ​​were eliminated and the average tensile strength was determined from the remaining five samples (Table 2 below).

[0146] [Table 2]

[0147] Conventional wisdom is that as the porosity of paper increases, the tensile strength decreases. For friction paper, it is desirable to have increased tensile strength without compromising porosity. Unexpectedly and unexpectedly, it has been found that the addition of PVP to the base paper pulp allows for such an increase in friction paper tensile values ​​while maintaining an acceptable porosity level. Approximately 10% by weight of PVP addition appears to provide optimal tensile performance.

[0148] Example 3 Preparation of Paper Suitable for Use as an Electrolyte Separator in Electrochemical Cells or as a Thermal Insulation or Flame Retardant Three types of aramid paper were produced from aramid polymer fibrils made from a mixture of PPD-T and PVP. The fibrils had Canadian Standard Freeness of 100 ml and 13.8 ml. 2The PPD-T / PVP fibrils consisted of 87 weight percent PPD-T and 13 weight percent PVP and had an average length-to-diameter ratio of about 2000. Each paper was prepared from an aqueous dispersion of 100% PPD-T / PVP fibrils in water. The aqueous dispersion was poured into a 21 x 21 cm handsheet mold with an additional 8 liters of water to form a wet-laid sheet. Each handsheet was then removed, placed between two pieces of blotter paper, couched by hand with a cotton swab, and dried in a handsheet dryer at 150°C for 10 minutes. The properties of the resulting paper structure are listed in Table 3.

[0149] The basis weights of the three papers were recorded. One paper was used as a control without the addition of PVP. Two aqueous PVP solutions were prepared by dissolving PVP in water. The first solution had a PVP concentration of 2.5% by weight, and the second solution had a PVP concentration of 5% by weight. A spray of PVP coating was then applied to the remaining two papers, the first paper sprayed with the first solution designated 3A, and the second paper sprayed with the second solution designated 3B. The PVP-coated papers were then dried overnight in an oven at 130° C. to crosslink the PVP. The exact PVP loading was determined by comparing the weight of the paper before and after the PVP was applied. The basic electrochemical properties are listed in Table 3 below. The crosslinking of PVP provided the paper with significantly higher tensile strength; however, it did not adversely affect the Gurley Hill porosity and average pore size, making items 3A and 3B suitable for use as separators or insulators in electrochemical cells.

[0150] Example 4 Preparation of electrochemical cells containing papers suitable for use as electrolyte separators or as thermal or flame insulating materials in electrochemical cells Separator papers 3A and 3B from Example 3 were used individually as battery separator papers in the fabrication of two battery cells. Each battery has (1) a cathode, (2) an anode, (3) a physical separation device between the cathode and anode to help prevent short circuits, and (4) some type of electrolyte. In the battery, battery separator papers 3A and 3B are positioned between the positive (cathode) and negative (anode) plates of the battery, providing structural separation between these electrodes of opposite charge while the electrolyte aids in the passage of electrical current through the separator.

[0151] [Table 3] The present disclosure encompasses the following preferred embodiments. <1> A paper suitable for use as a separator in an electrochemical cell or as a thermal or fire barrier; a) 90 to 99 weight percent aramid fiber pulp based on the total weight of the paper, the aramid fiber pulp comprising aramid polymer fibrils; The aramid polymer fibrils i) a diameter of 10 to 2000 nanometers; ii) a length between 0.2 and 3 mm; iii) a specific surface area of ​​3 to 40 square meters per gram; and iv) Canadian Standard Freeness from 0 to 100 milliliters Aramid fiber pulp having the formula: b) 1 to 10 weight percent polyvinylpyrrolidone, based on the total weight of the paper, the polyvinylpyrrolidone being present as a coating on the surfaces of the fibers. Includes The paper has a thickness of 10 to 40 micrometers and a tensile strength of at least 15 megapascals. <2> Has a tensile strength of 100 megapascals or less <1> The paper described in. <3> Average flow pore size of 0.01 to 0.5 micrometers <1> The paper described in. <4> The aramid polymer fibrils have a diameter of 10 to 1200 nanometers. <1> The paper described in. <5> The aramid polymer fibrils include poly(paraphenylene terephthalamide). <1> The paper described in. <6> The aramid polymer fibrils comprise a blend of polymers, the blend of polymers comprising greater than 50 weight percent poly(paraphenylene terephthalamide) and at least one other polymer. <2> The paper described in. <7> The aramid polymer fibrils comprise a blend of polymers, the blend of polymers comprising 80 to 96 weight percent poly(paraphenylene terephthalamide) and 4 to 20 weight percent poly(vinylpyrrolidone). <3> The paper described in. <8> Has a tensile strength of 100 megapascals or less <7> The paper described in. <9> Average flow pore size of 0.01 to 0.5 micrometers <7> The paper described in. <10> The aramid polymer fibrils have a diameter of 10 to 1200 nanometers. <7> The paper described in. <11> The paper further comprises aramid fibrids, the aramid fibrids being present in an amount up to 5 weight percent based on the weight of the aramid polymer pulp in the paper. <7> The paper described in. <12> Further includes aramid floc <7> The paper described in. <13> 1. An electrochemical cell or electrochemical cell module comprising paper as an electrolyte separator or as a thermal or flame barrier, said paper comprising: a) 90 to 99 weight percent aramid fiber pulp based on the total weight of the paper, the aramid fiber pulp comprising aramid polymer fibrils; The aramid polymer fibrils i) a diameter of 10 to 2000 nanometers; ii) a length between 0.2 and 3 mm; iii) a specific surface area of ​​3 to 40 square meters per gram; and iv) Canadian Standard Freeness from 0 to 100 milliliters Aramid fiber pulp having the formula: b) 1 to 10 weight percent polyvinylpyrrolidone, based on the total weight of the paper, the polyvinylpyrrolidone being present as a coating on the surfaces of the fibers. Includes The electrochemical cell or electrochemical cell module, wherein the paper has a thickness of 10 to 40 micrometers and a tensile strength of at least 15 megapascals. <14> The paper has a tensile strength of 100 megapascals or less. <13> Electrochemical cell according to claim 1. <15> The paper has an average flow pore size of 0.01 to 0.5 micrometers. <13> Electrochemical cell according to claim 1. <16> The aramid polymer fibrils have a diameter of 10 to 1200 nanometers. <13> Electrochemical cell according to claim 1. <17> The aramid polymer fibrils include poly(paraphenylene terephthalamide). <13> Electrochemical cell according to claim 1. <18> The aramid polymer fibrils comprise a blend of polymers, the blend of polymers comprising greater than 50 weight percent poly(paraphenylene terephthalamide) and at least one other polymer. <17> Electrochemical cell according to claim 1. <19> The aramid polymer fibrils comprise a blend of polymers, the blend of polymers comprising 80 to 96 weight percent poly(paraphenylene terephthalamide) and 4 to 20 weight percent poly(vinylpyrrolidone). <18> Electrochemical cell according to claim 1. <20> The paper has a tensile strength of 100 megapascals or less. <18> Electrochemical cell according to claim 1. <21> The paper has an average flow pore size of 0.01 to 0.5 micrometers. <18> Electrochemical cell according to claim 1. <22> The aramid polymer fibrils have a diameter of 10 to 1200 nanometers. <18> Electrochemical cell according to claim 1. <23> The paper further comprises aramid fibrids, the aramid fibrids being present in an amount up to 5 weight percent based on the weight of the aramid polymer pulp in the paper. <18> Electrochemical cell according to claim 1. <24> The paper further comprises aramid floc. <18> Electrochemical cell according to claim 1.

Claims

1. A paper suitable for use as a separator in an electrochemical cell or as a thermal or fire barrier; a) 90 to 99 weight percent aramid fiber pulp, based on the total weight of the paper, the aramid fiber pulp comprising aramid polymer fibrils; The aramid polymer fibrils i) a diameter between 10 and 2000 nanometers; ii) a length of 0.2 to 3 millimeters; iii) a specific surface area of ​​3 to 40 square meters per gram; and iv) Canadian Standard Freeness from 0 to 100 milliliters Aramid fiber pulp having the formula: b) 1 to 10 weight percent polyvinylpyrrolidone, based on the total weight of the paper, the polyvinylpyrrolidone being present as a coating on the surfaces of the fibers. Includes The paper has a thickness of 10 to 40 micrometers and a tensile strength of at least 15 megapascals or more.

2. 2. The paper of claim 1, wherein the aramid polymer fibrils comprise poly(paraphenylene terephthalamide).

3. 3. The paper of claim 2, wherein the aramid polymer fibrils comprise a blend of polymers, the blend of polymers comprising greater than 50 weight percent poly(paraphenylene terephthalamide) and at least one other polymer.

4. 4. The paper of claim 3, wherein the aramid polymer fibrils comprise a blend of polymers, the blend of polymers comprising 80 to 96 weight percent poly(paraphenylene terephthalamide) and 4 to 20 weight percent poly(vinylpyrrolidone).

5. 1. An electrochemical cell or electrochemical cell module comprising paper as an electrolyte separator or as a thermal or flame barrier, said paper comprising: a) 90 to 99 weight percent aramid fiber pulp, based on the total weight of the paper, the aramid fiber pulp comprising aramid polymer fibrils; The aramid polymer fibrils i) a diameter between 10 and 2000 nanometers; ii) a length of 0.2 to 3 millimeters; iii) a specific surface area of ​​3 to 40 square meters per gram; and iv) Canadian Standard Freeness from 0 to 100 milliliters Aramid fiber pulp having the formula: b) 1 to 10 weight percent polyvinylpyrrolidone, based on the total weight of the paper, the polyvinylpyrrolidone being present as a coating on the surfaces of the fibers. Includes The electrochemical cell or electrochemical cell module, wherein the paper has a thickness of 10 to 40 micrometers and a tensile strength of at least 15 megapascals or greater.

6. 6. The electrochemical cell of claim 5, wherein the aramid polymer fibrils comprise poly(paraphenylene terephthalamide).

7. 7. The electrochemical cell of claim 6, wherein the aramid polymer fibrils comprise a blend of polymers, the blend of polymers comprising greater than 50 weight percent poly(paraphenylene terephthalamide) and at least one other polymer.

8. 8. The electrochemical cell of claim 7, wherein the aramid polymer fibrils comprise a blend of polymers, the blend of polymers comprising 80 to 96 weight percent poly(paraphenylene terephthalamide) and 4 to 20 weight percent poly(vinylpyrrolidone).

Citation Information

Patent Citations

  • PVP / paralamide fiber and method for its manufacture

    JP1991069610A

  • Continuous method for making bicomponent fibers

    JP2008522055A

  • Paper comprising aramid pulp and a friction paper made therefrom

    US20190127918A1

  • High tensile strength paper suitable for use in electrochemical cells

    US20200056332A1